A Theory of Conglomerate Mergers - Mueller, Dennis C. (Quarterly Journal of Economics, 1969)
I. The growth maximization hypothesis, 644. — II. The demand and supply of firms when managers maximize stockholder welfare, 648. — III. The demand and supply of firms when managers and stockholders have different expectations, 653. — IV. Differences in discount rates as a cause of mergers, 654. — V. Growth maximization in light of recent merger history, 657.